Early college program implementation and growth: a collaborative initiative by a state university - Yavuz, Olcay; Milburn, Trudy (Concurrent Enrollment Review, 2025)
This article explores a collaborative initiative undertaken by a state university aimed at implementing and expanding an Early College Program. The conceptual framework, practical strategies, collaborative efforts and background of this initiative are presented. With a focus on improving college access for all, the article introduces the university's efforts to promote an inclusive Early College Program accessible to high-need students in particular. This collaborative approach highlights the importance of fostering collaboration among both internal and external partners of Institutions of Higher Education (IHE). By sharing insights into the program design and implementation, the article aims to inspire similar initiatives and contribute to the ongoing dialogue promoting early college experiences for all.
Keywords: Conceptual framework; Focus (optics); Focus group; Higher education; Program evaluation; State (computer science); dept.aa; dept.edl

Impact of supervision and evaluation on the professional development of school-based speech-language pathologists - Brown, Jacqueline; Trombly, Christopher; Roitsch, Jane (Perspectives of the ASHA Special Interest Groups, 2025)
Keywords: American Speech-Language-Hearing Association; Asha; Developmental psychology; Language development; Linguistics; Medical education; Medicine; Pedagogy; Professional development; Psychology; dept.edl

“Community hoarding”: a further complication for education research? - Arafeh, Sousan (2025)
Keywords: Computer science; Hoarding (animal behavior); Medicine; dept.edl

Polish and Indian teachers’ self-efficacy and attitudes towards inclusion of children and youth with disabilities in regular classrooms - Ćwirynkało, Katarzyna; Parchomiuk, Monika; Gregory, Jess; Ravi, Sunitha; Krishnamurthy, Sita (International Journal of Inclusive Education, 2025)
Keywords: Developmental psychology; Inclusion (mineral); Mainstreaming; Mathematics education; Pedagogy; Psychology; Self-efficacy; Social psychology; Sociology; Special education; Teachers; attitudes towards inclusion; dept.edl; inclusion; self-efficacy; students with disabilities